Power factor correction using capacitors & filters - Subramanian, Karthik; Tandon, Shantam (International Journal of Engineering and Technology, 2018)
Power factor is the ratio of the real current or voltage received by a load to the root mean square (rms) value of the current or voltage that was supposed to be acquired by the same load. The fact that the two become different is due to the presence of reactive power in the circuit which gets dissipated.Improving the power factor means reducing the phase difference between voltage and current. Since majority of the loads are of inductive nature, they require some amount of reactive power for them to function. Therefore, for the better use of electrical appliances with minimum amount of electrical consumption, the power factor should necessarily be increased and should be brought near to 1. This can be easily done by the help of Automatic Power Factor Correction Capacitors and Active filters.Â Â